Nacionalʺnyj stilʹ kak proâvlenie nacionalʹnogo âzyka serbov, horvatov,bošnâkov i černogorcev - Tošovič, Branko (Stylistyka, 2020)
This paper addresses the following ąuestions: 1) what is the national language, 2) what is the relation between national language and standard language, and 3) how and to what extent is the national style associated with the national language and standard language. According to the author, there are two basie types of national styles - literary (standard) and non-literary (nonstandard). Each national style characterizes two national markings - the expressive and functional stylistic. In the main part o f the analysis the basie expressive functional stylistic differences between the national styles of Śtokavian peoples (Serbs, Croats, Bosniaks and Montenegrins) are demonstrated.